Localization of Eigenvalues in Small Specified Regions of Complex Plane by State Feedback Matrix - H. Ahsani Tehrani (Journal of Sciences, Islamic Republic of Iran)
This paper is concerned with the problem of designing discrete-time control systems with closed-loop eigenvalues in a prescribed region of stability. First, we obtain a state feedback matrix which assigns all the eigenvalues to zero, and then by elementary similarity operations we find a state feedback which assigns the eigenvalues inside a circle with center   and radius. This new algorithm can also be used for the placement of closed-loop eigenvalues in a specified disc in z-plane for discrete-time linear systems. Some illustrative examples are presented to show the advantages of this new technique.